Seborrheic Dermatitis and Traditional Treatments - Tan Hoi, Huynh (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays, people are increasingly looking for traditional remedies to treat the disease with the desire to reduce the harmful side effects caused by the body in modern medicines. For scalp inflammation, many people wonder about this cure with oriental medicine. This is a skin disease that causes a lot of troubles in life, so learning about information and how to treat scalp inflammation is something that almost everyone should know. Despite this, the patient can still completely reduce the symptoms, restore skin, and enhance resistance against recurrent illness in the long run. One of the fastest ways to treat seborrheic dermatitis is to apply Western medicine products, including topical creams and oral medications. Each treatment has its advantages and disadvantages. However, herbs that are being used by traditional medications always show their very special role in the treatment of disease. This article focuses on the use of natural herbs to bring a better life for patients and help them have better skin and a pleasant spirit. This research paper was written in order to mention some effective solutions to make our lives a better place and to contribute to the development of the country.